2003
DOI: 10.1126/science.1082015
|View full text |Cite
|
Sign up to set email alerts
|

Role of Raf in Vascular Protection from Distinct Apoptotic Stimuli

Abstract: Raf kinases have been linked to endothelial cell survival. Here, we show that basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) differentially activate Raf, resulting in protection from distinct pathways of apoptosis in human endothelial cells and chick embryo vasculature. bFGF activated Raf-1 via p21-activated protein kinase-1 (PAK-1) phosphorylation of serines 338 and 339, resulting in Raf-1 mitochondrial translocation and endothelial cell protection from the intrinsic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
249
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(263 citation statements)
references
References 21 publications
12
249
0
1
Order By: Relevance
“…Upon VEGF binding, VEGFR2 undergoes dimerization and autophosphorylation at many tyrosine kinase residues (Dougher and Terman, 1999;Matsumoto et al, 2005), in which tyrosine phosphorylation at 1175 (or 1173 in mouse) activates the phospholipase Cg/protein kinase C pathway, leading to activation of the Raf/MEK/ERK signaling cascade (Guo et al, 1995;Xia et al, 1996;Matsumoto and Mugishima, 2006). The importance of the Raf/MEK/ERK signaling pathway in VEGFmediated angiogenesis is also supported by the finding that Raf-1 has a pivotal role in protecting endothelial cells from extrinsic-mediated apoptosis during angiogenesis (Alavi et al, 2003). In addition, our data are consistent with the finding that PD98059 is able to block the proliferation, migration and tube formation of endothelial cells in vitro (Wu et al, 2000;Srivastava et al, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Upon VEGF binding, VEGFR2 undergoes dimerization and autophosphorylation at many tyrosine kinase residues (Dougher and Terman, 1999;Matsumoto et al, 2005), in which tyrosine phosphorylation at 1175 (or 1173 in mouse) activates the phospholipase Cg/protein kinase C pathway, leading to activation of the Raf/MEK/ERK signaling cascade (Guo et al, 1995;Xia et al, 1996;Matsumoto and Mugishima, 2006). The importance of the Raf/MEK/ERK signaling pathway in VEGFmediated angiogenesis is also supported by the finding that Raf-1 has a pivotal role in protecting endothelial cells from extrinsic-mediated apoptosis during angiogenesis (Alavi et al, 2003). In addition, our data are consistent with the finding that PD98059 is able to block the proliferation, migration and tube formation of endothelial cells in vitro (Wu et al, 2000;Srivastava et al, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested that Raf-1 may promote cell survival by antagonizing the proapoptotic apoptosis signal-regulating kinase 1 (ASK1) through a direct inhibitory interaction with the N-terminal domain of ASK1 (Chen et al, 2001). It was also reported that Raf-1 translocates to the mitochondria in response to survival stimuli, where it mounts an antiapoptotic response independently of ERK activation (Wang et al, 1996;Salomoni et al, 1998;Peruzzi et al, 1999;Alavi et al, 2003). It was suggested that, when located to the mitochondria, Raf-1 suppresses cell death by inactivating the proapoptotic Bcl-2 family member Bad (Wang et al, 1996;Salomoni et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Using the Raf/MEK/ERK signalling pathway as paradigm, we have highlighted some of these mechanisms including differential protein interactions, subcellular compartmentalisation, different modes of activation, and differential targeting of downstream effectors. A recent study elegantly demonstrates how the cell orchestrates this repertoire of mechanisms (Alavi et al, 2003). In endothelial cells, vascular endothelial growth factor (VEGF) protects from apoptosis caused by serum starvation and DNA-damaging drugs, whereas basic fibroblast growth factor (bFGF) prevents the apoptosis induced by death receptor stimulation.…”
Section: Resultsmentioning
confidence: 99%